The N-Terminal Part of the Dishevelled DEP Domain Is Required for Wnt/β-Catenin Signaling in Mammalian Cells - Paclíková, Petra; Bernatík, Ondřej; Radaszkiewicz, Tomasz Witold; Bryja, Vítězslav (Molecular and cellular biology, 2017)
Dishevelled (DVL) proteins are key mediators of the Wnt/β-catenin signaling pathway. All DVL proteins contain three conserved domains: DIX, PDZ, and DEP. There is a consensus in the field that the DIX domain is critical for Wnt/β-catenin signaling, but contradictory evidence regarding the function of the DEP domain exists. It has been difficult, until recently, to test the importance of the DEP domain rigorously because of the interference with endogenous DVL, expressed in all Wnt-responsive cell lines. In this study, we took advantage of DVL knockout (DVL1/DVL2/DVL3 triple knockout) cells fully deficient in Wnt3a-induced signaling events and performed a series of rescue experiments. Using these complementation assays, we analyzed the role of individual DVL isoforms. Further domain mapping of DVL1 showed that both the DVL1 DEP domain and especially its N-terminal region are required and sufficient for Wnt3a-induced phosphorylation of LRP6 and TopFlash reporter activation. On the contrary, multiple DEP domain mutants deficient in the planar cell polarity (PCP) pathway could fully rescue the Wnt3a response. This study provides conclusive evidence that the DVL DEP domain is essential for Wnt/β-catenin signaling in mammalian cells and establishes an experimental system suitable for further functional testing of DVL.
Keywords: CRISPR/Cas; DEP domain; Wnt3a; Dishevelled; Wnt/β-catenin signaling